Sestavljanje enojezičnega slovarja za domače govorce - Hanks, Patrick (Jezik in slovstvo, 2009)
In the article we compare the role of the dictionary and the lexical database, and address the issue of language register and correctness in dictionaries. We then deal with various types of sense distribution in dictionaries, the history of the word, and the principles of selection of dictionary headwords. We cite the corpus as an essential source for the treatment of meaning, collocation and syntagmatics, and investigate ways of interpreting corpus data - corpus profiling of headwords. We conclude with the thought that a dictionary represents the central language standard, whereby all of the expressed linguistic opinions contained in it must be based on corpus evidence.
Keywords: Corpus linguistics; korpusno jezikoslovje; računalniško jezikoslovje; computational linguistics; leksikografija; lexicography; slovarji; enojezični slovarji